Association between educational level and postoperative delirium in older patients undergoing abdominal surgery: a two-sample cohort study - Mingju Xiang; Jie Liu; Jing Wang; Feng Li; Tingting Fan; Jia Tang (Frontiers in Medicine)
BackgroundPostoperative delirium (POD) is a critical complication in older patients following abdominal surgery, significantly contributing to delayed recovery and prolonged hospital stays. Understanding the risk factors associated with POD is essential for developing effective prevention and intervention strategies. This study investigates the potential impact of educational attainment on the incidence of delirium in this patient population.MethodsThis study utilized a two-sample cohort design to collect demographic and educational attainment, and clinical data, including, from older patients undergoing abdominal surgery. The assessment of delirium during the recovery phase was conducted using the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) and the 3-Minute Diagnostic Interview for Confusion Assessment Method within the first three postoperative days. In the exploratory cohort, the relationship between education and postoperative delirium was determined by univariate analysis, followed by multivariate logistic regression to determine that education was an independent predictor. The identified risk factors were subsequently validated in an independent validation cohort to ensure robustness and generalizability.ResultsThe exploratory cohort consisted of 342 cases, while the validation cohort included 150 cases. Exploratory cohort regression analysis identified lower educational attainment and procedures or anesthesia lasting longer than 4 h as independent risk factors for POD. Anesthesia time of more than 4 h was also an independent risk factor for delirium during resuscitation.ConclusionLower educational attainment is significantly related to an increased chance of POD in older adults undergoing abdominal procedures. These findings suggest that preoperative assessments should incorporate educational level as a potential risk factor, providing a basis for targeted prevention and intervention strategies to mitigate POD.